Mucoepidermoid carcinoma in a thyroglossal duct remnant. (2015) - Warner, E.; Ofo, E.; Connor, S.; Odell, E.; Jeannon, J.P.
Highlights: Thyroglossal duct remnants should be surgically excised, if possible due to the risk of malignant transformation. Mucoepidermoid carcinomas can present in diverse locations outside of salivary glands. A high index of suspicion for malignancy is required with neck masses in adults, especially following a period of rapid growth. If aggressively treated, patients with mucoepidermoid carcinoma outside of salivary glands may still have a favourable prognosis. Abstract: Introduction: Thyroglossal duct cysts (TDC) are common midline neck swellings resulting from embryological remnants of the thyroglossal duct. They often contain ectopic thyroid tissue and malignant transformation has been reported, most commonly to papillary thyroid carcinoma. Mucoepidermoid carcinoma (MEC) usually occurs in the salivary glands and only rarely in the thyroid. This is the first case of a MEC occurring within a thyroglossal duct remnant. Presentation of a case: A 73 year old lady presented with a thyroglossal duct cyst. She declined surgical excision, as she was adamant she wanted to avoid surgery. The neck mass rapidly enlarged at two years following initial diagnosis. Fine needle aspiration cytology was suspicious for carcinoma. She underwent total thyroidectomy and selective central compartment neck dissection with adjuvant radiotherapy. She remains alive and well two years post treatment. Discussion: Mucoepidermoid carcinoma is the most common malignant neoplasm of salivary glands, although it has rarely been reported in diverse locations including the thyroid, lung and pancreas. To the best of our knowledge, this is the first reported case of mucoepidermoid carcinoma arising from a thyroglossal duct remnant. Conclusion: This case adds weight to the literature favouring surgical excision of thyroglossal duct remnants due to the risk of malignant transformation.